Experience of orbital floor fractures in a UK level one trauma centre: a focus on the surgical approach and lid-related complications. Issue 4 (May 2022) - Borghol, Khaled; Turton, Natalie; Sharp, Ian
Abstract: The two surgical approaches to access orbital fractures are transconjunctival and transcutaneous. The aim of this study was to assess the outcomes of orbital repairs with a focus on lid-related complications and their management. A retrospective analysis was carried out over a five-year period (January 2015 to January 2020) to assess all consecutive orbital repairs in our unit. Data were collected for variables including demographics, fracture pattern, surgical approach, and details of postoperative complications. A total of 111 patients were included in the study, 94 were male (85%), the majority being between 16 and 45 years of age. A total of 46 (41%) had isolated orbital floor fractures, 31 (28%) zygomaticomaxillary complex, and 18 (16%) Le Fort pattern fractures. Eighty per cent (n = 91) received a transconjunctival approach as first choice. In the transconjunctival group, six (6.6%) had entropion and increased scleral show, four (4.4%) had ectropion, and none had canthal malposition. In the transcutaneous group (n = 20) there was a higher rate of ectropion (25%, n = 5), a lower rate of entropion (n = 1, 5%) and higher rate of increased scleral show (n = 2, 10%). Factors associated with a higher rate of complications included complex fractures, use of conjunctival sutures, and increased length of time to surgery. Seventy-two per cent of patients who suffered entropion required further surgical treatment. The most common complication of the transconjunctival approach was entropion, and clinicians should have a low threshold for early surgical management. We feel that this should be part of the consenting process, especially in high-risk cases.